The COVID-19 lockdown as a model of detraining in division 1 college softball players - Zeppieri Jr., G.; Hung, C.-J.; Pazik, M.; Moser, M.; Farmer, K.; Pozzi, F. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background The COVID-19 pandemic interrupted the organized training of softball players, similar to the abrupt cessation of sports participation that can happen after an injury. Thus, the COVID-19 pandemic offers a unique model to study how sudden detraining influences softball players.